A reappraisal of theMiddle Triassic chirotheriid Chirotherium ibericus Navás, 1906 (Iberian Range NE Spain), with comments on the Triassic tetrapod track biochronology of the Iberian Peninsula - Díaz Martínez, Ignacio (2015)
Fil: Díaz Martínez, Ignacio. Universidad Nacional de Río Negro. Sede Alto Valle; Argentina